1981
DOI: 10.1515/znc-1981-1-209
|View full text |Cite
|
Sign up to set email alerts
|

Medium-Induced Formation of Indole Alkaloids and Concomitant Changes of Interrelated Enzyme Activities in Cell Suspension Cultures of Catharanthus roseus

Abstract: Recently medium conditions have been developed which stimulate the formation of the indole alkaloid ajmalicine in cell suspension cultures of Catharanthus roseus [6]. When cells were subjected to these conditions the alkaloid accumulation was preceded by a 12-fold increase of the specific activity of tryptophan decarboxylase. The enzyme activity showed a maximum two days after the cell transfer into the induction medium and subsequently declined. In contrast the activity of strictosidine synthase, the enzyme c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
0

Year Published

1985
1985
1998
1998

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…This enzyme activity is highly regulated in seedlings and is consistent with previous observations in cell suspension cultures (6)(7)(8). The work with cell suspension cultures has demonstrated that induction of TDC did not always result in the accumulation of indole alkaloids (7)(8) whereas the accumulation of tabersonine in etiolated seedlings coincided with the induction of the TDC enzyme activity (3). This suggests that although the developmental program for tabersonine biosynthesis is tightly coupled in seedlings, and TDC appears to be a rate-limiting step, the two events can be dissociated in tissue culture systems.…”
Section: Discussionsupporting
confidence: 92%
“…This enzyme activity is highly regulated in seedlings and is consistent with previous observations in cell suspension cultures (6)(7)(8). The work with cell suspension cultures has demonstrated that induction of TDC did not always result in the accumulation of indole alkaloids (7)(8) whereas the accumulation of tabersonine in etiolated seedlings coincided with the induction of the TDC enzyme activity (3). This suggests that although the developmental program for tabersonine biosynthesis is tightly coupled in seedlings, and TDC appears to be a rate-limiting step, the two events can be dissociated in tissue culture systems.…”
Section: Discussionsupporting
confidence: 92%
“…The enzyme TDC3 (EC 4.1.1.28) converts Trp to tryptamine in plants (13). Tryptamine provides the indole unit of monoterpenoid-indole and derived alkaloids.…”
mentioning
confidence: 99%
“…This peak in TDC activity is followed by an almost immediate accumulation of alkaloid end products (1, 5). TDC activity is also highly regulated in Catharanthus and Cinchona cell culture, where under certain conditions, transient activation of the enzyme can occur (8,13,16,21). The appearance of this enzyme in Catharanthus cultures has been shown to be preceded by transient appearance of TDC mRNA after induction by fungal elicitors (20).…”
mentioning
confidence: 99%
“…The enzyme has previously been characterized and purified to homogeneity from cell suspension cultures of Catharanthus roseus (18) indole alkaloids ajmalicine and catharanthine. It has been speculated that expression of TDC is the controlling factor for alkaloid production in Catharanthus cell suspension cultures (14,19). However, recent studies suggest that although expression of TDC is highly regulated in plant tissue cultures (5,8,9,14,17), as in intact plants (4,6), appearance of TDC enzyme activity in culture does not always result in the accumulation of indole alkaloids (9,15).…”
mentioning
confidence: 99%